Penerapan Terapi Psikoreligius : Zikir Terhadap Tanda dan Gejala Serta Kemampuan Mengatasi Halusinasi: Implementation of Psychoreligius Therapy: Dhikr to Signs, Symptoms and Ability Overcoming hallusination - Madepan Mulia Madepan; Julita Sari; Dewi Damayanti (Madago Nursing Journal, 2021)
Introduction: Mental disorders are brain disorders characterized by disruption of emotions, thought processes, behavior and perceptions. Auditory hallucinations are hearing voices or noises in the form of less loud noises to clear words talking about the client, even to a complete conversation between two or more people where the client is told to do something that is sometimes dangerous. Useful Aim: This study aims to see the signs and symptoms of auditory hallucinations and the ability to overcome hallucinations in schizophrenic patients after being given psychoreligious therapy: dhikr in the Abung Kunang Community Health Center, North Lampung Regency. Research Methods: Using the method of giving nursing actions in the form of psychoreligious therapy: remembrance of 2 schizophrenic patients who experienced auditory hallucinations nursing problems. Reported in the form of case studies. Results: The results obtained were a decrease in signs and symptoms of hallucinations and an increase in the patient's ability to cope with hallucinations. Suggestion: Nurses are expected to provide the optimal application of psychoreligious therapy: dhikr to patients who have auditory hallucinations nursing problems.